The Photovoltaic Performance based on Radiation Intensity Examination using Experimental Study and Thermal Simulation - Prasetyo, Singgih Dwi; Taufik Ulhakim, Muhamad (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2024)
Solar energy is a renewable energy source that can be converted into electrical energy through photovoltaic (PV) solar cells. However, the efficiency is low, with only 15-20% depending on solar irradiation converted into electricity. The angle of the sun and the structural position of the solar cell system also affect the amount of solar radiation received. Research has been carried out to determine the effect of radiation intensity on the performance of PV solar cells using experimental methods and thermal simulation. The temperature distribution of PV cells has been studied using experimental studies and thermal simulations. The highest temperature was produced at a solar radiation intensity of 1100 W/m2 of 68.4 ⸰C for the experimental study and 69.4 ⸰C for the thermal simulation study. The highest efficiency is produced at a radiation intensity of 1000 W/m2, with the highest efficiency being 11.5%. This study analyzes the impact of radiation intensity on the electrical efficiency of solar PV cells using two-way ANOVA. The radiation intensity has a P-value of 1.85E-05, which indicates an influence on the electricity produced. There is an MS value of research variation smaller than the MS error of 7.22E-07, indicating an interaction between the two variables